Nutritional geometry of calcium and phosphorus nutrition in broiler chicks. Growth performance, skeletal health and intake arrays. (19th May 2014) - Bradbury, E. J.; Wilkinson, S. J.; Cronin, G. M.; Thomson, P. C.; Bedford, M. R.; Cowieson, A. J.
Abstract : The interaction between calcium (Ca) and non-phytate phosphorus (nPP) in broiler nutrition and skeletal health is highly complex with many factors influencing their digestion, absorption and utilisation. The use of an investigative model such as the geometric framework allows a graphical approach to explore these complex interactions. A total of 600 Ross 308-day-old male broiler chicks were allocated to one of 15 dietary treatments with five replicates and eight birds per replicate. Dietary treatments were formulated to one of three total densities of total Ca+nPP; high (15 g/kg), medium (13.5 g/kg) and low (12 g/kg) and at each density there were five different ratios of Ca : nPP (4, 2.75, 2.1, 1.5 and 1.14 : 1). Weekly performance data was collected and at the end of the experiment birds were individually weighed and the right leg removed for tibia ash analysis. Skeletal health was assessed using the latency to lie (LTL) at day 27. At low Ca and high nPP as well as high Ca and low nPP diets, birds had reduced feed intake, BW gain, poorer feed efficiency and lower tibia ash, resulting in a significant interaction between dietary Ca and nPP ( P <0.05). LTL times were negatively influenced by diets having either a broad ratio (high Ca, low nPP) or too narrow a ratio (low Ca, high nPP) indicating that shorter LTL times may be influenced by the ratio of Ca : nPP rather than absolute concentrations of either mineral. The calculated intake arrays show that broilers more closely regulate Ca intake than nPP intake. Broilers are willing to over consume nPP to defend a Ca intake target more so than they are willing to over consume Ca to defend an nPP target. Overall dietary nPP was more influential on performance metrics, however, from the data it may appear that birds prioritise Ca intake over nPP and broadly ate to meet this requirement. As broilers are more willing to eat to a Ca intake target rather than an nPP intake target, this emphasises the importance of formulating diets to a accurately balanced density of Ca : nPP considering the biological importance of both minerals.